If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + -3(x + 2y) = y + 1 4x + (x * -3 + 2y * -3) = y + 1 4x + (-3x + -6y) = y + 1 Combine like terms: 4x + -3x = 1x 1x + -6y = y + 1 Reorder the terms: 1x + -6y = 1 + y Solving 1x + -6y = 1 + y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6y' to each side of the equation. 1x + -6y + 6y = 1 + y + 6y Combine like terms: -6y + 6y = 0 1x + 0 = 1 + y + 6y 1x = 1 + y + 6y Combine like terms: y + 6y = 7y 1x = 1 + 7y Divide each side by '1'. x = 1 + 7y Simplifying x = 1 + 7y
| (2a^2+3y)= | | 2-10=20 | | 2(7x+3)=-3 | | 5m^2-20=2m^3-8m | | 5x^2=-220 | | 9y-8-5y+7=0 | | 15x+18y= | | (2/3)x-5=x/6 | | (6y+7)-(6+5y)=11 | | -0.10(47)+0.80x=0.05(x-4) | | (-7c*-4)+8x=12+14 | | 3(1-9x)+4x= | | 3/7-2=20 | | x/3-x=-12-2x/9 | | 8x+(9x-5)= | | 4x-6-3x=16-20 | | 38=-x-6x-4 | | ((-3)-(-2)(9))= | | 8-2(4-x)=2x+3x | | 24=-2x-x-3 | | 3x+2x=200 | | 2=.3x-.5x-7 | | (y/9)=(8/5) | | G(x)=2x^2-8x+4 | | 7x-7=2x | | 105=4x+4x+9 | | 8v+5(4v-10)= | | A=(95)(61) | | 2.4p-16=3.4p-11 | | y/9=8/5 | | 9x-2x+3=x-8+11 | | 2x-3+4=0 |